LexArt Les mots de la peinture France, Allemagne, Angleterre, Pays-Bas, 1600-1750 - Heck, Michèle-Caroline (Théorie des Art, 2018)
LexArt. The words of painting is a dictionary of terms and concepts, which, from the artistic literature, in a synchronous approach of discourse and artistic practice, describe the painting as it is practiced in France, Germany, England and the Netherlands in the 17th and 18th centuries. These writings constitute the mental, intellectual and visual universe, which makes it possible to better apprehend the work of art, and shape the eye to better see. The purpose of this book is to highlight the stakes of uses resituated in different contexts in time and space, in a confrontation of ways of thinking, painting and watching. Seventy-seven essays address nearly two hundred and fifty notions. The articles respond to each other, and form an ensemble which, behind the alphabetical order of the dictionary, draws the contours of a new reading of the painting seen through the eye of the painter and the eye of the spectator. Indeed, the "speaking painting" does not only introduce the viewer into the painter's studio by showing him the "how to do", he introduces him into the painting itself, shows him what to see and how see.